Identification of Compatible Shade Tolerant Fodder Suited Under Ailanthus excelsa - Ravi, R.; Divya, M. P.; Mohan Raj, T.; Krishnan, P. Ratha (Indian Forester, 2011)
In order to select the compatible shade tolerant fodder crops under Ailanthus excelsa Roxb. studies were carried out at Forest College and Research Institute, Mettupalayam (T.N.) by planting four shade tolerant fodder crops viz., cowpea, sorghum, Desmanthus and Stylosanthus under fifteen year old Ailanthus trees. The observations revealed that the growth and yield of the test crops were reduced under intercropping when compared to pure cropping. Among the test crops, Desmanthus was most affected and fodder cowpea was the least affected. So fodder cowpea is identified as a best compatible fodder suited under Ailanthus excelsa.